Hierarchically Designed SiOx/SiOy Bilayer Nanomembranes as Stable Anodes for Lithium Ion Batteries. (2nd May 2014) - Zhang, Lin; Deng, Junwen; Liu, Lifeng; Si, Wenping; Oswald, Steffen; Xi, Lixia; Kundu, Manab; Ma, Guozhi; Gemming, Thomas; Baunack, Stefan; Ding, Fei; Yan, Chenglin; et al.
<x xml:space="preserve">Abstract</x> Hierarchically designed SiOx/SiOy rolled‐up bilayer nanomembranes are used as anodes for lithium‐ion batteries. The functionalities of the SiO(x, y) layers can be engineered by simply controlling the oxygen content, resulting in anodes that exhibit a reversible capacity of about 1300 mA h g−1 with an excellent stability of over 100 cycles, as well as a good rate capability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>